Problems and potential solutions to drug shortages - I. R. Svechkareva; D. E. Shilova; M. I. Baranova (Реальная клиническая практика: данные и доказательства)
In recent years, the number of drug shortages has increased both locally and internationally. The sudden and unpredictable occurrence of drug shortages negatively affects the daily lives of healthcare workers and patients. Physicians are sometimes forced to prescribe alternative treatments considered less effective or even less well tolerated. These alternatives make it more difficult for patients to adhere to treatment and increase the risk of medication errors.